Forced vibration of time-varying elevator traction system - Sun, Jie (Strojniški vestnik, 2024)
This paper proposes a theoretical model for the forced vibration of time-varying elevator traction systems caused by eccentric excitation of the traction machine. Based on the Hamilton principle and a variational principle with variable boundaries, the equations of motion and the complex boundary condition of a time-varying elevator traction system are established. A quantitative formula between the angular velocity of the traction machine, the diameter of the traction wheel, the elevator running distance and the running time is put forward. It is found that when the maximum values of acceleration and deceleration exceed 1.5 m/s2, the elevator traction system may undergo resonance.
Keywords: časovna spremenljivost; dinamika; dvigalni pogonski sistem; dynamics; elevator traction system; Galerkinova metoda; Hamiltonovo načelo; numerical analysis; numerična analiza; pojav; time-varying; vibracije; vibration